ผลการจัดการเรียนรู้ตามองค์ประกอบของทักษะปฏิบัติที่มีต่อทักษะการสอนด้านอยู่อย่างพอเพียงของนักศึกษาระดับบัณฑิตศึกษา: The Effects of Practical Skills Approach Learning Management on The Instructional Skills in Sufficient Life of Graduate Students - Pornsiri Eiamguaw, พรสิริ เอี่ยมแก้ว (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2021)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาทักษะการสอนด้านอยู่อย่างพอเพียงของนักศึกษาระดับบัณฑิตศึกษาที่ได้รับการจัดการเรียนรู้ตามแนวการสอนทักษะปฏิบัติ 2) เปรียบเทียบทักษะการสอนด้านอยู่อย่างพอเพียงก่อนเรียนและหลังเรียนของนักศึกษาระดับบัณฑิตศึกษาที่ได้รับการจัดการเรียนรู้ตามแนวการสอนทักษะปฏิบัติ 3) เปรียบเทียบทักษะการสอนด้านอยู่อย่างพอเพียงของนักศึกษาระดับบัณฑิตศึกษาที่ได้รับการจัดการเรียนรู้ตามแนวการสอนทักษะปฏิบัติกับเกณฑ์ร้อยละ 75 ของคะแนนเต็ม กลุ่มตัวอย่างที่ใช้วิจัยคือนักศึกษาระดับบัณฑิตศึกษา หลักสูตรประกาศนียบัตรบัณฑิต สาขาวิชาชีพครู ภาคพิเศษ ที่เรียนอยู่ในภาคเรียนที่ 2 ปีการศึกษา 2561 จำนวน 30 คน ซึ่งได้มาจากการสุ่มตัวอย่างแบบกลุ่ม เครื่องมือที่ใช้ในการวิจัยครั้งนี้ ได้แก่ 1) แผนการจัดการเรียนรู้ตามแนวการสอนทักษะปฏิบัติ จำนวน 3 แผน ที่มีคุณภาพความเหมาะสมระดับมากที่สุด 2) แบบประเมินทักษะการสอนด้านอยู่อย่างพอเพียง มีค่าดัชนีความสอดคล้องเท่ากับ 1 และค่าดัชนีความสอดคล้องระหว่างผู้ประเมินเท่ากับ 0.79 วิเคราะห์ข้อมูลโดยหาค่าเฉลี่ย และทดสอบค่าที ผลการวิจัย พบว่า 1. นักศึกษาระดับบัณฑิตศึกษาที่ได้รับการจัดการเรียนรู้ตามแนวการสอนทักษะปฏิบัติมีทักษะการสอนด้านอยู่อย่างพอเพียงอยู่ในระดับดี ( =2.86,S.D.=0.25) 2. นักศึกษาระดับบัณฑิตศึกษาที่ได้รับการจัดการเรียนรู้ตามแนวการสอนทักษะปฏิบัติมีทักษะการสอนด้านอยู่อย่างพอเพียงหลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3. นักศึกษาระดับบัณฑิตศึกษาที่ได้รับการจัดการเรียนรู้ตามแนวการสอนทักษะปฏิบัติ มีทักษะการสอนด้านอยู่อย่างพอเพียงสูงกว่าเกณฑ์ร้อยละ 75ของคะแนนเต็มอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 The purposes of this research were to 1) study the instructional skills in sufficient life of graduate students with practical skills approach learning management 2) compare the instructional skills in sufficient life of graduate students before and after learning by practical skills approach learning management and 3) compare the instructional skills in sufficient life of graduate students with practical skills approach learning management with the criteria 75 percent of full score. The sample was 30 graduate students of Graduate Diploma Program in Teaching Profession, Special Program in the second of 2018 academic year which selected by random cluster sampling method. The research instruments were 1) the 3 lesson plans practical skills approach learning management with the most appropriate and 2) the assessment test of the instructional skills in sufficient life, the IOC index was 1 and the Rater Agreement Index (RAI) was 0.79. Data were analyzed by mean and dependent t-test. The results of the research showed that 1. The graduate students with practical skills approach learning management had instructional skills in sufficient life at the good level ( =2.86, S.D.=0.25) 2. The graduate students after learning with practical skills approach learning management was higher than before significantly by statistical level .05. 3. The graduate students after learning with practical skills approach learning management was higher than the criteria 75 percent of full score significantly by statistical level .05.